Dielectric and microstructural behaviour of strontium titanate borosilicate glass ceramic system - Thakur O.P.; Kumar D.; Parkash O.M.; Pandey L. (My University, 2025)
65(SrO·TiO2)-35(2SiO2·B2O3) wt% glass was synthesized. Differential thermal analysis study shows one exothermic peak which shifts towards higher temperature with increasing heating rate. Glass ceramics prepared by controlled crystallization of strontium titanate borosilicate glass produce uniform distribution of crystallites in a glassy matrix. Attempt was made to crystallize strontium titanate phase in this glass ceramic. Different phases precipitated out during ceramization have been identified by X-ray diffraction. It appears that due to high reactivity of SrO with B2O3, strontium borate crystallizes as principal phase followed by TiO2 (rutile) and Sr3Ti2O7 phases. Dielectric constant of these glass ceramics was observed to be more or less temperature independent over wide range of temperatures with low values of dielectric constant and dissipation factor. © 1995 The Indian Academy of Sciences.